Menggagas Collaborative Governance untuk Pengelolaan Sampah yang Lebih Baik di Desa Bacem, Kabupaten Blitar - Wydha Mustika Maharani; Ferida Asih Wiludjeng; Aditya Aji Santoso (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The increase in population without the support of adequate waste management facilities, such as the availability of Temporary Shelters (TPS), has caused the people of Blitar Regency to have the habit of throwing rubbish carelessly in rivers or the habit of burning rubbish. This can cause various negative impacts on the environment and health. This research highlights the importance of the